The Influence of Co-Firing Coal with Biomass Syngas on the Thermodynamic Parameters of a Boiler - Jin Wang; Qiaopeng Yao; Xiaoling Jin; Lei Deng (Applied Sciences, 2023)
Biomass syngas can be considered as a supplementary fuel to partially substitute coal, which is beneficial to CO2 emission reduction. For the case study, the influences of co-firing typical biomass syngas (gasification from palm, straw, and wood) with coal on the thermodynamic parameters of a 300 MW tangentially fired boiler are evaluated through a thermal calculation based on the principles of mass conservation, heat conservation, and heat transfer. The effects of boiler loads, biomass syngas species, and consumption rates are discussed. The results show that the introduction of biomass syngas weakens the radiative characteristics of the flame and reduces the furnace exit flue-gas temperature. As 3 × 104 m3 h−1 of wood syngas is introduced, the decrement of thermal efficiency reaches 0.4%, while that of the coal consumption rate is 5.1%. The retrofitting of the boiler was not necessary and the corrosion of the low-temperature heating surface did not appear. The CO2 annual emission reduction could achieve 0.001 to 0.095 million tons for palm syngas, 0.005 to 0.069 million tons for straw syngas, and 0.013 to 0.107 million tons for wood syngas with increasing biomass syngas consumption rates under the full load. Moreover, the main thermodynamic parameters changed more significantly under the low loads.